The Effect of Dipeptidyl Nitrile Derivatives on Pancreatic Ductal Adenocarcinoma Cells In Vitro - Botelho, Sabrina M.; dos Reis Rocho, Fernanda; Cianni, Lorenzo; Montanari, Carlos A.; Leitão, Andrei (Current Chemical Biology, 2021)
Aims: This study aims to evaluate the bioactivity of dipeptidyl nitrile inhibitors of human cysteine cathepsins that could work as anticancer agents in a drug discovery and development project. Background: Human lysosomal cysteine proteases promote cancer progression, migration, and metastasis, targeted by inhibitors. Objective: Here, 19 cysteine protease inhibitors known as dipeptidyl nitriles were tested using MIA PaCa-2 pancreatic cancer cells and Balb/3T3 clone A31 non-tumoral mouse fibroblasts. Methods: In vitro assays evaluated cell migration, colony formation, inhibition of the enzymatic activity in cell lysates, and combination therapy with gemcitabine. Results: There were mixed results; the inhibitors reduced the number of colonies but did not affect the total area. Cells migrated despite enzyme inhibition by Neq0709 and Neq0712. As expected, the compounds were non-cytotoxic; they improved the potency of gemcitabine in the combined therapy assay, especially for Neq0707. Conclusion: In summary, our findings revealed the complexity of dealing with the translation from biochemical to cell-based assays in the hit-to-lead step.
Keywords: cysteine protease inhibition